Study on Burr Formation at the Top Edge in Rectangular Groove Cutting - Wen Jun Deng; Zi Chun Xie; Ping Lin; Tong Kui Xu (Advances in Materials Science and Engineering)
Previous research on burr formation in machining operations has usually been limited to the study of the rollover burr in the cutting direction. In this paper, a 3D finite element model to simulate rectangular groove cutting operation has been developed using commercial finite element software, employing experimentally determined mechanical properties at elevated strain rates and temperatures. The plastic deformation behavior and three-dimensional burr formation during rectangular groove cutting is investigated. The simulated burr profile and cutting force prove that the developed model can capture the thermo-mechanical mechanisms in rectangular groove cutting and can simulate burr development with considerable accuracy. The study concentrates on the influence of cutting parameters on burr formation which are also conducted. The results show that the feed rate and rake angle are the cutting parameters which have a major influence on burr size in the groove cutting operation. And the effect of cutting velocity and minor clearance angle in the traditional range on burr size are quite limited.